Transformation of Property Concept in the West - Görem Bora Zencirkıran (İnsan & Toplum)
Though areas such as law currently see it as a mere subject of technical investigation, property is an important concept for justifying capitalism. The idea or assumption that transition to capitalism from feudalism—as it is defined in European history—requires a transformation of values, is useful for the explanation of property’s conceptual transformation. This article follows that transformation from classical writers’ conceptions of virtue to post-Financial Revolution era’s political theorization within different philosophical texts. Also, it is argued that the transformation of property is not a complete break from the conception, thinking of it as a premise for freedom can be a sign of continuity in mentioned philosophers.